Synergistic anti-cancer effects via co-delivery of TNF-related apoptosis-inducing ligand (TRAIL/Apo2L) and doxorubicin using micellar nanoparticles - Lee, A.; Dhillon, S.; Wang, Y.; Pervaiz, Shazib; Fan, W.; Yang, Y. (2011)
The use of small molecule drugs in cancer chemotherapy has mostly been limited by dose-dependent toxicity and development of drug resistance resulting from repeated administrations. To overcome such problems, efforts have been made to develop drug delivery systems that can bear multiple therapeutic agents in one system. The purpose of this study is to deliver human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (Apo2L/TRAIL) and doxorubicin (Dox, an anti-cancer drug) with micellar nanoparticles self-assembled from a biodegradable cationic copolymer P(MDS-co-CES) to achieve synergistic cytotoxic effects in cancer cells. Exogenously expressed TRAIL using recombinant methods shows great potential in cancer therapy as it induces cell death selectively in cancer cells with limited toxicity to normal tissues. Dox-loaded nanoparticles and TRAIL formed stable nanocomplexes with a size of ~225 nm and zeta potential of ~70 mV. Effects of nanocomplexes on both wild type and TRAIL-resistant SW480 colorectal carcinoma cells were investigated. The assemblies of Dox and TRAIL with P(MDS-co-CES) nanoparticles were efficiently delivered to cancer cells. Receptor-blocking studies showed that the nanocomplexes entered cells via death receptor-mediated endocytosis. Synergism in cell death induction was analysed by the isobologram method to study drug interactions. Cytotoxicity of the nanocomplexes to non-cancerous cells was significantly lower than cancerous cells. Anti-proliferative effects of nanocomplexes were retained in remaining cancer cells in long-term cultures after treatment with the nanocomplexes. In summary, this Dox and TRAIL co-delivery system can be a promising candidate for cancer treatment. © The Royal Society of Chemistry 2011.